Design and Development of Augmented Reality Learning Application on Dentistry - Wan Rusli, Wan Nur Aishah Hanis (Applied Information Technology And Computer Science, 2023)
This purpose of this study was to develop a basic dental learning smartphone app for kids utilising Augmented Reality. With the advancement of technology, the mobile application technique enables students to more simply and effectively apply their teaching and learning. Posters, pamphlets, and booklets may be outmoded due to constant connectivity through mobile devices, making them ineffective in conveying information and promoting awareness among youngsters. The raw data from interviews has been vetted by experts. This application was built utilising Agile Methodology. The approach was designed for mobile devices and allows for easy integration of multimedia components like as 3D models, music, and animation. This initiative would target primary school student aged 6 to 12 to help educate basic dental principles.